On a collection of crabs (Crustacea: Decapoda: Brachyura) from Mozambique, Africa - Willems, Max; Fransen, Charles H.j.m. (Zootaxa, 2026)
This monograph focuses on a collection of previously unidentified brachyuran crabs (Crustacea: Decapoda: Brachyura), present in the Naturalis Biodiversity Center (formerly Rijksmuseum van Natuurlijke Historie), Leiden, the Netherlands. All the examined material was collected between 1982 and 1987 from the mangroves and the littoral zone around Inhaca Island, Mozambique, Africa. A total of 1162 specimens are identified. The specimens belong to 90 different species of crabs from 26 families. Five new records of crab species for Mozambican waters are found: Hiplyra elegans (Gravier, 1920), Hiplyra variegata (Rüppell, 1830), Pseudomicippe tenuipes A. Milne-Edwards, 1865, Medaeops neglectus (Balss, 1922) and Chaenostoma crassimanus Stimpson, 1858.